Biocompatibility and hyperthermia cancer therapy of casein‐coated iron oxide nanoparticles in mice. (26th February 2020) - Bani, Milad Salimi; Hatamie, Shadie; Haghpanahi, Mohammad
Abstract : Magnetic nanoparticles (MNPs) can be used as heat generation source in cancer hyperthermia therapy. While iron oxide nanoparticles (NPs) are the most popular choice for magnetic hyperthermia, adding a surface enhancement can improve its performance. Furthermore, for MNPs to be used in biomedical application their cytotoxicity needs to be evaluated. In this study biocompatibility and also in vivo performance of casein‐coated MNPs were assessed. Cell viability of normal cell lines in all of tests remained above 95% for 0.5 and 1 mg/mL concentration and even the minimum recorded cell viability for normal cell lines was 84.78% at 20 mg/mL concentration. In contrast cell viability of cancer cell lines in contact with casein coated MNPs core‐shell structure except for one sample remained below 85%. By introduction of and alternating magnetic field, cell viability of samples with lower MNP concentration dropped by 20% to 30% while this drop for samples with higher concentration was 10% to 20%. Furthermore, results of in vivo trials show that just 1 week of hyperthermia treatment with casein coated MNPs core‐shell structure can reduce the tumor size of the mice by 33%. Real‐time polymerase chain reaction results further confirmed the effectiveness of this method. Moreover, findings of this study suggest that lower injection speed can improve NPs distribution and treatment effect. Results of this study suggest that core‐shell structure can positively affect the tumor growth and the combination of good biocompatibility, innate hostility toward cancer cells and good heating power makes them a good candidate for hyperthermia cancer therapy applications.